Efektivitas Layanan Bimbingan Kelompok Menggunakan Teknik Assertive Training Dalam Meningkatkan Kepercayaan Diri Siswa Kelas X Di SMAN 6 Pandeglang Tahun Ajaran 2025/2026 - Nur Fadilah Hartini; Muhamad Ikhsan; Fitri Arnita (Universitas Veteran Bangun Nusantara, 2025)
This study aims to determine the effectiveness of group counseling services using the assertive training technique in improving the self-confidence of tenth-grade students at SMA Negeri 6 Pandeglang in the 2025/2026 academic year. Self-confidence is an individual's belief in their ability to face various situations and challenges. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The sample consisted of 20 students divided into experimental and control groups. The experimental group received group counseling treatment using the assertive training technique, while the control group received no treatment. The self-confidence questionnaire used had a reliability coefficient of 0.958. Data were analyzed through normality, homogeneity, and t-tests. The results showed a significance value of Sig. (2-tailed) = 0.000 < 0.05, indicating a significant difference between the experimental and control groups. Therefore, the assertive training technique is effective in improving students’ self-confidence.